2016
DOI: 10.4238/gmr.15017866
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CYP17 gene polymorphisms and risk of prostate cancer

et al.

Abstract: ABSTRACT. Cytochrome P450 17a-hydroxylase (CYP17) plays a critical role in androgen biosynthesis. Polymorphisms of the CYP17 promoter have been proposed as risk factors for prostate cancer; however, some studies have produced inconclusive or controversial results. We investigated the relationship between polymorphisms of the CYP17 gene and the risk of prostate cancer. A total of 176 patients with prostate cancer were enrolled in the study, and 168 healthy individuals acted as the control group. The participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Our results were in agreement with Konstantinos et al, who suggested that the C allele of (T/C) polymorphism may provide additional promoter activity with an increased rate of CYP17 mRNA transcription [22]. The polymorphism is thought to induce CYP17 gene expression resulting in higher levels of androgens and, consequently, in a higher risk of the development and progression of prostate disease [23], [24].…”
Section: Discussionsupporting
confidence: 92%
“…Our results were in agreement with Konstantinos et al, who suggested that the C allele of (T/C) polymorphism may provide additional promoter activity with an increased rate of CYP17 mRNA transcription [22]. The polymorphism is thought to induce CYP17 gene expression resulting in higher levels of androgens and, consequently, in a higher risk of the development and progression of prostate disease [23], [24].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a study engaged by Konstantinos et al, confirms our results by suggesting that the C allele of rs743572 polymorphism might influence promoter activity with an increased amount of CYP17A1 mRNA transcription (27) . The rs743572 polymorphism increases the levels of androgen due to the induction of CYP1A1 gene expression that ultimately resulted in the development and progression of prostate disorders (28) .…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] It has been considered that rs743572 SNP is related to the expression of CYP17; T allele might induce the upregulation of CYP17 in patients with prostate cancer. [ 25 ] However, the effects of rs743572 on endometriosis were not clear.…”
Section: Discussionmentioning
confidence: 99%